Neck circumference cutoff point as a predictor of metabolic syndrome in Brazilian rural workers - Manoela Cassa Libardi; Cleodice Alves Martins; Júlia Rabelo Santos Ferreira; Glenda Blaser Petarli; Monica Cattafesta; Olívia Maria de Paula Alves Bezerra; Eliana Zandonade; Carlos Eduardo Gomes Siqueira; Luiz Carlos de Abreu; Jonathan Filippon; Luciane Bresciani Salaroli (PLoS ONE, 2025)
Neck circumference (NC) is a predictive measure for the diagnosis of Metabolic Syndrome (MS). The aim of the present study was to establish cutoff points for NC as a predictor of the presence of MS in Brazilian rural workers, based on the MS components according to the IDF and NCEP-ATP III criteria. This is a cross-sectional study carried out with rural workers in the municipality of Santa Maria de Jetibá, in the state of Espírito Santo, Brazil. The ROC curve was calculated and the cutoff points for predicting the risk of developing MS were stipulated from the NC, identified by the area under the curve, using different methods of criteria for determining MS. Sensitivity, specificity, positive and negative predictive values and Youden index were applied. The significance level adopted was 5%. The cutoff points were different for males, resulting in 39.550 cm (AUC 0.832) according to the NCEP-ATP III criterion and 39.125 cm (AUC 0.888) according to the IDF criterion. For women, the cutoffs were similar, resulting in a single cutoff of 34.725 cm (AUC 0.862 for NCEP-ATP III and 0.849 for IDF). The cutoff points defined for men and women for NC showed good sensitivity and specificity for predicting MS in the studied population. The NC measurement proved to be a simple, low-cost and accurate measure for assessing this morbidity in Brazilian rural workers.